Fast-charging AA-type or AAA-type lithium ion battery
By using lithium iron phosphate positive electrode material, integrated charging interface and optimized battery cell structure in AA or AAA lithium-ion batteries, the existing lithium-ion batteries have been solved, and the fast charging function and good Cyclic performance.
Patent Information
- Application Number
- CN202411609905.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Existing AA or AAA lithium-ion batteries are costly and inconvenient to use, and require a dedicated charger, which affects the user experience.
A fast-charging AA type or AAA type lithium ion battery is designed, using lithium iron phosphate as the positive electrode material, integrating a charging interface and a charging protection circuit, and a positive electrode sheet, a negative electrode sheet, a diaphragm and an electrolyte are installed in the battery cell. By optimizing the ineffective porosity and electrolyte density of the positive and negative electrode diaphragms, charging efficiency and cycling stability are improved.
It realizes a low-cost and easy-to-use fast charging lithium-ion battery, with good rate performance and cycle performance, which can meet fast charging needs and extend battery life.
Smart Images

Figure CN119447506A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a fast-charging AA or AAA lithium ion battery. Background Art
[0002] AA or AAA batteries are widely used in various portable small electronic devices and household appliances. They are divided into primary batteries and secondary batteries. Primary batteries have certain recycling pollution problems. Secondary batteries are usually used in some applications with high frequency of use. Secondary batteries include nickel-cadmium batteries, nickel-metal hydride batteries, and lithium-ion batteries. However, since the voltage of the former two is 1.2V, their application is limited. The voltage of lithium-ion batteries can reach 3.7V, which can completely replace primary batteries and has high energy density. At present, the AA or AAA secondary lithium-ion batteries on the market usually use positive electrode materials such as lithium cobalt oxide and nickel cobalt manganese oxide, which are relatively expensive. In addition, the AA or AAA secondary lithium-ion batteries on the market usually need to be equipped with a dedicated charger, which makes it inconvenient to use and has a poor experience.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The present invention provides a fast-charging AA or AAA lithium-ion battery, aiming to provide an AA or AAA lithium-ion battery with an integrated charging interface and a battery, a fast-charging function, low cost and a long life.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a fast-charging AA or AAA lithium-ion battery, comprising a housing, a battery cell arranged in the housing, a control circuit board, an upper sealing cover and a lower sealing cover for sealing the housing; the battery cell comprises an upper positive terminal and a lower negative terminal; a positive electrode cap is welded on the top of the control circuit board, a positive electrode connecting piece is welded on the bottom of the control circuit board, and the positive electrode connecting piece is abutted against the positive terminal; the positive electrode cap penetrates the upper sealing cover and seals the control circuit board between the upper sealing cover and the battery cell together with the upper sealing cover; a charging interface and a charging protection circuit are arranged on the control circuit board, and a socket adapted to the charging interface is arranged on the housing or the upper sealing cover;
[0007] The battery cell is provided with a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet includes a positive electrode collector and a positive electrode film provided on at least one surface of the positive electrode collector and including lithium iron phosphate. The negative electrode sheet includes a negative electrode collector and a negative electrode film provided on at least one surface of the negative electrode collector and including graphite.
[0008] Porosity of the positive electrode membrane H c % is less than 15%, the ineffective porosity H c% is defined as the ratio of the volume of invalid pores in the positive electrode membrane to the total volume of the positive electrode membrane. Invalid pores refer to the volume of the space in the positive electrode membrane that cannot be infiltrated by the electrolyte except for the lithium iron phosphate body.
[0009] The density of the electrolyte is 1.1~1.25g / cm 3 .
[0010] In some embodiments of the present invention, the ineffective pore porosity H of the negative electrode membrane is a % is 9~14%, the ineffective pore porosity H a % is defined as the ratio of the volume of ineffective pores in the negative electrode membrane to the total volume of the negative electrode membrane. Ineffective pores refer to the volume of the space in the negative electrode membrane other than the graphite body that cannot be wetted by the electrolyte.
[0011] In some embodiments of the present invention, the battery cell satisfies at least one of the following conditions 1 to 7:
[0012] Condition 1: Porosity H of the ineffective pores of the positive electrode membrane c % satisfies 8% to 12%;
[0013] Condition 2: Porosity H of the ineffective pores of the positive electrode membrane c % and the ineffective porosity H of the negative electrode membrane a %Satisfy H a % / H c % = 1.12 ~ 1.17;
[0014] Condition 3: Compacted density PD of positive electrode c 2.25~2.40g / cm 3 ;
[0015] Condition 4: Compacted density PD of negative electrode a 1.40~1.60g / cm 3 ;
[0016] Condition 5: Invalid Porosity in, PD c The compaction density of the positive electrode; ρ c is the true density of lithium iron phosphate, which is 3.6 g / cm 3 ; V S is the electrolyte absorption volume per unit mass of the positive electrode membrane, in cm 3 / g;
[0017] Condition 6: Invalid Porosity in, PD a is the compaction density of the negative electrode; ρ a is the true density of graphite, which is 2.26 g / cm 3 ; V s is the electrolyte absorption volume per unit mass of the negative electrode membrane, in cm 3 / g;
[0018] Condition seven: The electrolyte comprises, by mass percentage, 13% to 15% lithium salt, 5% to 6% additives and 79% to 81% solvents, wherein the solvent comprises at least one of ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, fluorobenzene and ethyl acetate; the additive comprises at least one of vinylene carbonate, vinyl sulfate, propane sultone, fluoroethylene carbonate and lithium difluorophosphate; and the lithium salt is LiPF6.
[0019] In some embodiments of the present invention, the battery cell satisfies at least one of the following conditions eight to fourteen:
[0020] Condition 8: The positive electrode current collector is aluminum foil;
[0021] Condition 9: The negative electrode current collector is copper foil;
[0022] Condition 10: The positive electrode membrane also includes a positive electrode binder and a positive electrode conductor, and the mass ratio of lithium iron phosphate, positive electrode conductor and positive electrode binder is 95-97:1.5-2.5:1-3; the positive electrode binder is PVDF, and the positive electrode conductor is at least one of carbon black, acetylene black, carbon nanotubes and graphene.
[0023] Condition 11: The negative electrode membrane also includes a negative electrode binder and a negative electrode conductor, and the mass ratio of graphite, negative electrode conductor and negative electrode binder is 94.5-96.5:1-2:1-1.8:0.9-2; the negative electrode binder is at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid binder, and the negative electrode conductor is at least one of carbon black, acetylene black, carbon nanotubes and graphene.
[0024] Condition 12: The electrolyte injection coefficient is 2.6-3.2 g / Ah;
[0025] Condition 13: The specific surface area of lithium iron phosphate is 10-15m 2 / g, tap density TD is 0.8~1.5g / cm 3 ;
[0026] Condition 14: The BET surface area of graphite is 1 to 2.2 m 2 / g, tap density TD is 1~1.3g / cm 3 .
[0027] In some embodiments of the present invention, a negative electrode connecting piece is disposed between the negative electrode terminal and the lower sealing cover, and one end of the negative electrode connecting piece abuts against the negative electrode terminal, and the other end of the negative electrode connecting piece abuts against the lower sealing cover.
[0028] In some embodiments of the present invention, the lithium ion battery further satisfies at least one of the following characteristics 1 to 4:
[0029] Feature 1: The charging protection circuit includes a voltage stabilizing circuit and a charging control circuit;
[0030] Feature 2: A first insulating device is provided between the upper sealing cover and the control circuit board;
[0031] Feature 3: A second insulating device is provided between the control circuit board and the battery cell;
[0032] Feature 4: The charging interface is Lightning interface or Type C interface.
[0033] In a second aspect, the present invention provides a method for preparing a battery cell in any of the above embodiments, comprising the following steps:
[0034] (1) lithium iron phosphate, a positive electrode conductive agent, a positive electrode binder and a solvent 1 are mixed to prepare a positive electrode slurry, the positive electrode slurry is coated on a positive electrode current collector, and the positive electrode sheet is obtained after drying, pressing, slitting and sheeting;
[0035] (2) mixing graphite, a negative electrode conductive agent, and a negative electrode binder, adding solvent 2 and stirring to prepare a negative electrode slurry, coating the negative electrode slurry on a negative electrode current collector, drying, pressing, slitting, and sheeting to obtain a negative electrode sheet;
[0036] (3) stacking the positive electrode sheet, the separator, and the negative electrode sheet in order and winding them to form a bare cell;
[0037] (4) The bare battery cell is fixed in the steel shell by spot bottom welding, and the electrolyte is injected after drying. Then, the battery cell is obtained by cap welding, sealing, standing, degassing, forming and aging.
[0038] In some embodiments of the present invention, drying and pressing comprises: drying the current collector coated with the positive electrode slurry or the negative electrode slurry until the weight loss is 50% to 90% of the weight loss when dried to constant weight, taking it out for pressing; then continuing to dry to constant weight, and pressing again.
[0039] In some embodiments of the present invention, the pressing conditions are: the pressing temperature is lower than 25° C., the pressing pressure is 0.1 to 0.5 MPa, and the pressing time is 60 to 120 s.
[0040] In some embodiments of the present invention, solvent 1 is N-methylpyrrolidone NMP, and solvent 2 is deionized water.
[0041] The present invention has the following beneficial effects:
[0042] (1) The present invention provides a rechargeable AA or AAA lithium-ion battery, which is provided with a charging interface. The charging interface is integrated with the battery and is easy to use.
[0043] (2) The lithium-ion battery provided by the present invention uses lithium iron phosphate as the positive electrode active material, which has a low cost.
[0044] (3) The positive electrode membrane on the positive electrode plate of the lithium-ion battery provided by the present invention has a low ineffective pore porosity and good rate performance, which can meet the fast charging requirements of the battery.
[0045] (4) The battery cell provided by the present invention has both good rate performance and cycle stability, and has good adaptability as an AA or AAA battery. The AA or AAA battery prepared therefrom has good fast charging performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0047] Figure 1 It is a schematic diagram of the structure of the lithium-ion battery of the present invention.
[0048] Figure 2 It is a schematic diagram of the cross-section structure of the battery cell of the present invention;
[0049] In the figure: 1. Shell; 2. Battery cell; 3. Control circuit board; 4. Upper sealing cover; 5. Lower sealing cover; 21. Positive terminal; 22. Negative terminal; 31. Positive cap; 32. Positive connecting piece; 33. Type C charging port; 11. Jack; 6. Negative connecting piece; 21. Positive electrode piece; 22. Negative electrode piece; 23. Diaphragm. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0051] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0052] Reference to "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments.
[0053] In the embodiment of the present application, the term "or / and" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A or / and B can represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0054] In addition, the character “ / ” in this article generally indicates that the previous and next associated objects are in an “or” relationship.
[0055] In the embodiments of the present application, "multiple" means more than two (including two). Similarly, "multiple groups" means more than two groups (including two groups), and "multi-layer" means more than two layers (including two layers), unless otherwise clearly specified and limited.
[0056] In the embodiments of the present application, "at least one" means one or more than one.
[0057] In the embodiments of the present application, the orientations or positional relationships indicated by the technical terms "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed in a specific orientation, etc., and cannot be understood as limiting the embodiments of the present application. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application according to specific circumstances.
[0058] The present invention provides a fast-charging AA-type or AAA-type lithium-ion battery, comprising a housing, a battery cell arranged in the housing, a control circuit board, and an upper sealing cover and a lower sealing cover for sealing the housing; a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte are arranged in the battery cell; the positive electrode sheet comprises a positive electrode collector and a positive electrode film arranged on at least one surface of the positive electrode collector and comprising lithium iron phosphate; the negative electrode sheet comprises a negative electrode collector and a negative electrode film arranged on at least one surface of the negative electrode collector and comprising graphite; the ineffective pore porosity H of the positive electrode film is c % is less than 15%, the ineffective porosity Hc % is defined as the ratio of the volume of invalid pores in the positive electrode membrane to the total volume of the positive electrode membrane. Invalid pores refer to the volume of the space in the positive electrode membrane that cannot be infiltrated by the electrolyte except for the lithium iron phosphate body. The density of the electrolyte is 1.1-1.25 g / cm 3 .
[0059] At present, the fast-charging batteries used in commercial consumer electronic products are usually layered positive electrode materials such as lithium cobalt oxide, lithium nickel cobalt manganese oxide, etc. These positive electrode materials contain Co metal and are relatively expensive. However, lithium iron phosphate is expected to gradually replace layered positive electrode materials in the 3C field due to its wide source of raw materials, low price, and high safety performance. However, due to the self-limiting nature of the spinel structure of lithium iron phosphate positive electrode materials, its lithium ion transmission efficiency is low, so the charging and discharging speed is low.
[0060] The present invention provides a battery cell with fast charging performance and lithium iron phosphate as the positive electrode material, which is suitable for AA or AAA lithium ion batteries. The density of the electrolyte in the battery cell is 1.1-1.25 g / cm 3 , the ineffective porosity H of the positive electrode membrane c % is lower than 15%, so it has a higher charging efficiency, the 14C constant current ratio is maintained above 90%, and the capacity retention rate after 600 cycles at 4C rate is maintained above 96%.
[0061] Ineffective pore porosity H c %
[0062] The volume of the positive electrode membrane includes the volume of lithium iron phosphate, conductive agent, adhesive, and pores, wherein the pores also include open pores and closed pores. The present invention defines the pores that cannot be wetted by the electrolyte as closed pores, and the pores that can be wetted by the electrolyte as open pores; therefore, the volume of the space in the membrane that cannot be wetted by the electrolyte except the lithium iron phosphate body includes the volume of the conductive agent, adhesive, and closed pores; that is, Among them, V T is the total unit mass volume of the membrane (cm 3 / g), PD c The compaction density of the positive electrode sheet (g / cm 3 );V H is the unit mass volume excluding the lithium iron phosphate body (cm 3 / g), ρ c is the true density of lithium iron phosphate (the value is 3.6g / cm 3 ),Right now V S is the electrolyte absorption volume per unit mass of the positive electrode membrane (cm 3 / g).
[0063] The lower the ineffective pore porosity of the positive electrode membrane, the more lithium iron phosphate active materials or the fewer closed pores. The more lithium iron phosphate active materials, the larger the capacity, and the fewer closed pores, the better the wettability of the electrolyte to the positive electrode membrane. Both are beneficial to improving the lithium ion transmission efficiency of the positive electrode sheet and improving its rate performance, thereby achieving fast charging.
[0064] Since the ineffective pore porosity of the positive electrode membrane is related to the compaction density of the positive electrode membrane and the electrolyte absorption, the preparation process and the density of the electrolyte have a great influence on it. The density of the electrolyte provided by the present invention is 1.1-1.25 g / cm 3 In this density range, the electrolyte has good wettability to the electrode sheet, reducing the closed pores of the positive electrode membrane.
[0065] In some embodiments of the present invention, the ineffective pore porosity H of the negative electrode membrane is a % is 9~14%.
[0066] Similarly, the ineffective porosity H of the negative electrode membrane a % The calculation method is the same as that of the positive electrode membrane, and H a The smaller the %, the more conducive it is to the insertion and extraction of lithium ions, and the better it is for improving its rate performance.
[0067] In some embodiments of the present invention, the ineffective pore porosity H of the positive electrode membrane is c % satisfies 8% to 12%; within this range, the positive electrode film can take into account both good rate performance and cycle performance. c % should not be too low, as too low indicates that there is too little conductive agent or adhesive. The former will reduce the conductivity, while the latter will reduce the bonding strength between components and between the membrane and the current collector, making it easy for them to separate from each other as the cycle progresses, resulting in increased internal resistance.
[0068] In some embodiments of the present invention, the ineffective pore porosity H of the positive electrode membrane is c % and the ineffective porosity H of the negative electrode membrane a %Satisfy H a % / H c % = 1.12 ~ 1.17. Meeting this range of values can ensure that during the charge and discharge process, the lithium ion deintercalation rate in the positive electrode is balanced with the lithium ion deintercalation rate in the negative electrode, thereby meeting the fast charging demand and avoiding the occurrence of lithium precipitation or increased internal resistance due to inconsistent lithium ion deintercalation rates, thereby ensuring the service life and safety of the battery.
[0069] In some embodiments of the present invention, the compaction density PD of the positive electrode sheet is c 2.25~2.40g / cm 3 .
[0070] In some embodiments of the present invention, the compaction density PD of the negative electrode sheet is a 1.40~1.60g / cm 3 .
[0071] In some embodiments of the present invention, the electrolyte comprises, by mass percentage, 13% to 15% lithium salt, 5% to 6% additives and 79% to 81% solvent, the solvent comprising at least one of ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, fluorobenzene and ethyl acetate; the additive comprises at least one of vinylene carbonate, vinyl sulfate, propane sultone, fluoroethylene carbonate and lithium difluorophosphate; and the lithium salt is LiPF6.
[0072] In some embodiments of the present invention, the positive electrode current collector is aluminum foil.
[0073] In some embodiments of the present invention, the negative electrode current collector is copper foil.
[0074] In some embodiments of the present invention, the positive electrode membrane also includes a positive electrode binder and a positive electrode conductor, and the mass ratio of lithium iron phosphate, positive electrode conductor and positive electrode binder is 95-97:1.5-2.5:1-3; the positive electrode binder is polyvinylidene fluoride PVDF, and the positive electrode conductor is at least one of carbon black, acetylene black, carbon nanotubes and graphene.
[0075] In some embodiments of the present invention, the negative electrode membrane also includes a negative electrode binder and a negative electrode conductor, and the mass ratio of graphite, negative electrode conductor and negative electrode binder is 94.5-96.5:1-2:1-1.8:0.9-2; the negative electrode binder is at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid binder, and the negative electrode conductor is at least one of carbon black, acetylene black, carbon nanotubes and graphene.
[0076] In some embodiments of the present invention, the electrolyte injection coefficient is 2.6 to 3.2 g / Ah.
[0077] In some embodiments of the present invention, the specific surface area of lithium iron phosphate is 10 to 15 m 2 / g, tap density TD is 0.8~1.5g / cm 3 .
[0078] In some embodiments of the present invention, the specific surface area of graphite is 1 to 2.2 m 2 / g, tap density TD is 1~1.3g / cm 3 .
[0079] In some embodiments of the present invention, a negative electrode connecting piece is disposed between the negative electrode terminal and the lower sealing cover, and one end of the negative electrode connecting piece abuts against the negative electrode terminal, and the other end of the negative electrode connecting piece abuts against the lower sealing cover.
[0080] In some embodiments of the present invention, the charging protection circuit includes a voltage stabilization circuit and a charging control circuit.
[0081] In some embodiments of the present invention, a first insulating device is provided between the upper sealing cover and the control circuit board.
[0082] In some embodiments of the present invention, a second insulating device is provided between the control circuit board and the battery cell.
[0083] In some embodiments of the present invention, the charging interface is a Lightning interface or a Type C interface, preferably a Type C interface.
[0084] A second aspect of the present invention provides a method for preparing a battery cell according to any one of the above embodiments, comprising the following steps:
[0085] (1) lithium iron phosphate, a positive electrode conductive agent, a positive electrode binder and a solvent 1 are mixed to prepare a positive electrode slurry, the positive electrode slurry is coated on a positive electrode current collector, and the positive electrode sheet is obtained by drying, pressing, slitting and sheeting;
[0086] (2) Graphite, a negative electrode conductive agent, and a negative electrode binder are mixed, solvent 2 is added, and the mixture is stirred to prepare a negative electrode slurry, the negative electrode slurry is coated on a negative electrode current collector, and the negative electrode sheet is obtained after drying, pressing, slitting, and sheeting;
[0087] (3) stacking the positive electrode sheet, the separator, and the negative electrode sheet in order and winding them to form a bare cell;
[0088] (4) The bare battery cell is fixed in the steel shell by spot bottom welding, and the electrolyte is injected after drying. Then, the battery cell is obtained by cap welding, sealing, standing, degassing, forming and aging.
[0089] In some embodiments of the present invention, drying and pressing comprises: drying the current collector coated with the positive electrode slurry or the negative electrode slurry until the weight loss is 50% to 90% of the weight loss when dried to constant weight, taking it out for pressing; then continuing to dry to constant weight, and pressing again. Preferably, the pressing conditions are: the pressing temperature is lower than 25°C, the pressing pressure is 0.1 to 0.5 MPa, and the pressing time is 60 to 120 seconds.
[0090] In the prior art, the current collector coated with the positive / negative electrode slurry is usually dried to constant weight and then cold pressed to obtain a pole piece. The principle of controlling the compaction density is that by controlling the surface density of the coating process and the cold pressing thickness to obtain a pole piece with a certain compaction density, this method will produce more closed pores, thereby increasing the ineffective pore porosity of the pole piece. The present invention creatively cold presses the pole piece with liquid, and the positive electrode membrane on the pole piece with liquid retains a certain fluidity. Cold pressing it can rearrange the components in the membrane, which is conducive to the discharge of gas in the closed pores, thereby reducing the closed pores. It should be noted that cold pressing the current collector coated with the positive / negative electrode slurry when the weight loss is 50% to 90% of the weight loss when dried to constant weight is a result with better effect obtained through a large number of tests, because if the weight loss rate is greater than 90%, the effect of reducing the closed pores is low, and if the weight loss rate is less than 50%, the membrane is too fluid and easy to stick to the roller. In addition, the effect of cold pressing is better than that of hot pressing, that is, using a roller with a temperature lower than 25°C during pressing is conducive to the rapid hardening of the membrane surface at the moment the roller contacts the membrane to prevent sticking. After the electrode is dried to a constant weight, cold pressing is performed again to control the compaction density.
[0091] In some embodiments of the present invention, solvent 1 is N-methylpyrrolidone NMP, and solvent 2 is deionized water.
[0092] Example 1
[0093] A fast-charging AA or AAA lithium-ion battery, see Figure 1 , comprising a shell 1, a battery cell 2 arranged in the shell, a control circuit board 3, an upper sealing cover 4 arranged at the top of the shell and a lower sealing cover 5 arranged at the bottom of the shell; the battery cell 2 comprises a positive terminal 21 at the top and a negative terminal 22 at the bottom; a positive cap 31 is welded on the top of the control circuit board 3, and a positive connecting piece 32 is welded on the bottom of the control circuit board 3, and the positive connecting piece 32 abuts against the positive terminal 21 of the battery cell 2; the positive cap 31 penetrates the upper sealing cover 4 and seals the control circuit board 3 between the upper sealing cover 4 and the battery cell 2 with the upper sealing cover 4; a Type C charging interface 33 and a charging protection circuit are arranged on the control circuit board 3, and the charging protection circuit is electrically connected to the Type C charging interface 33, and a socket 11 compatible with the Type C charging interface 33 is arranged on the shell 1; a negative connecting piece 6 is arranged between the negative terminal 22 of the battery cell 2 and the lower sealing cover 5, and one end of the negative connecting piece 6 abuts against the negative terminal 22, and the other end of the negative connecting piece 6 abuts against the lower sealing cover 5; the charging protection circuit comprises a voltage stabilizing circuit and a charging control circuit.
[0094] Cell 2 structure reference Figure 2, a positive electrode sheet 21, a negative electrode sheet 22 and a separator 23 are provided, the electrolyte is filled between the positive electrode sheet 21, the negative electrode sheet 22 and the separator 23, the positive electrode sheet 21 includes a positive electrode collector and a positive electrode film arranged on at least one surface of the positive electrode collector and including lithium iron phosphate, the negative electrode sheet 22 includes a negative electrode collector and a negative electrode film arranged on at least one surface of the negative electrode collector and including graphite.
[0095] Porosity of the positive electrode membrane H c % is 10.37%, and the ineffective pore porosity H of the negative electrode membrane a % is 11.20%, that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the polar membrane are H c % / H a %=1.08.
[0096] The filling coefficient of battery cell 2 is 2.82 g / Ah.
[0097] The density of the electrolyte is 1.17 g / cm 3 , calculated by mass percentage, includes the following components: 80.5% solvent, 5.5% additive, 14% LiPF6; the solvent is a mixture of ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and ethyl acetate in a mass ratio of 6:2:1:1, and the additive is a mixture of vinylene carbonate, fluoroethylene carbonate, and lithium difluorophosphate in a mass ratio of 4:1:1.
[0098] The preparation of the above-mentioned battery cell 2 comprises the following steps:
[0099] (1) Preparation of positive electrode sheet 21: PVDF is dissolved in N-methylpyrrolidone (NMP) to obtain a uniform slurry, and then carbon nanotubes and carbon black SP are dispersed in the slurry in turn by ultrasonic-assisted mechanical stirring, and finally lithium iron phosphate is added to perform slurrying and sieving under vacuum conditions to obtain a positive electrode slurry with a viscosity of 7522 mPa·s; the mass ratio of lithium iron phosphate, carbon black SP, carbon nanotubes, and PVDF is 95.4:1.5:0.5:2.6; slurrying refers to homogenizing the slurry at room temperature using a stirring paddle that can move up and down, with a stirring speed of 500 rpm and a time of 0.5 h; the BET specific surface area of lithium iron phosphate is 12.4 m 2 / g, tap density TD is 1.1g / cm 3 ; The positive electrode binder PVDF manufacturer is SOLVAF, carbon black SP, and carbon nanotube manufacturer is Yiruishi Graphite and Carbon.
[0100] The positive electrode slurry was then scraped onto both sides of the aluminum foil to obtain a positive electrode coating, which was then placed in an oven at 80°C and dried until the weight loss of the positive electrode coating reached 50% to 60% of the weight loss when dried to constant weight. The positive electrode coating was then taken out for cold pressing, and then vacuum dried at 120°C to constant weight. The compacted density was 2.31 g / cm 3 The positive electrode sheet; the cold pressing temperature is 25°C, the pressure is 0.2MPa, and the cold pressing time is 60s.
[0101] (2) Preparation of negative electrode sheet 22: Graphite, carbon black SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR are mixed in a mass ratio of 95.5:1.5:1.2:1.8, deionized water is added and stirred under vacuum to prepare a negative electrode slurry with a solid content of 50%; the specific surface area of the graphite is 1.74 m 2 / g, tap density TD is 1.16g / cm 3 The CMC manufacturer is Japan Daicel, and the SBR manufacturer is Japan Aiyulong.
[0102] The negative electrode slurry was uniformly coated on both sides of the copper foil to obtain a negative electrode coating, which was placed in an oven at 80°C and dried until the weight loss of the negative electrode coating reached 60% to 70% of the weight loss when dried to constant weight. Then, the negative electrode coating was taken out for cold pressing, and then vacuum dried at 120°C to constant weight. After cutting, the compacted density was 1.5 g / cm 3 The negative electrode sheet; the cold pressing temperature is 25°C, the pressure is 0.2MPa, and the cold pressing time is 60s.
[0103] (3) The positive electrode sheet 21, the separator 23, the negative electrode sheet 22 and the like are stacked in order and wound to form a bare cell. The bare cell is fixed in the steel shell by spot bottom welding, and after drying, the electrolyte is injected according to the injection coefficient, and then the cap is welded, sealed, left to stand, degassed, formed and aged to obtain the cell 2. The separator is a ceramic-coated PP separator with a thickness of 12 μm.
[0104] The electrolyte absorption volume per unit mass of the positive and negative electrode membranes is determined by:
[0105] The positive electrode sheet or negative electrode sheet (hereinafter referred to as "electrode sheet") and the corresponding current collector are cut into 50mm×50mm sheets to be tested, dried at 85℃ to constant weight and weighed. The electrode sheet sample is recorded as m E0 , the current collector sample is denoted as m C0 ; Place the sample to be tested in a sealed bottle and add electrolyte (density is ρ, unit is g / cm 3 ) immerse the sample to be tested and seal it. After soaking for 24 hours, take it out with tweezers and gently wipe the surface liquid with filter paper and weigh it. The pole piece sample is recorded as m E1 , the current collector sample is denoted as mC1 , that is, the electrolyte absorption volume per unit mass of the positive or negative electrode membrane Each pole piece sample was tested at least 3 times, and a parallel test of the current collector was set up for each test, and the average value of the obtained Vs was taken.
[0106] The V S =0.1080cm 3 / g, V of negative electrode film s =0.1520cm 3 / g.
[0107] Example 2
[0108] The difference from Example 1 is that the ineffective pore porosity H of the positive electrode membrane is c % is 9.58%; that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the positive electrode membrane are H a % / H c %=1.17.
[0109] When preparing the positive electrode sheet, the current collector coated with the positive electrode slurry is dried until the weight loss of the positive electrode coating reaches 70% to 80% of the weight loss when dried to constant weight, and then taken out for cold pressing. The compacted density of the obtained positive electrode sheet is 2.28 g / cm 3 , V of the positive electrode film S =0.1166cm 3 / g.
[0110] Example 3
[0111] The difference from Example 1 is that the ineffective pore porosity H of the positive electrode membrane is c % is 8.35%; that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the positive electrode membrane are H a % / H c %=1.34.
[0112] When preparing the positive electrode sheet, the current collector coated with the positive electrode slurry is dried until the weight loss of the positive electrode coating reaches 60% to 70% of the weight loss when dried to constant weight, and then taken out for cold pressing. The compacted density of the obtained positive electrode sheet is 2.35 g / cm 3 , V of the positive electrode film S =0.1100cm 3 / g.
[0113] Example 4
[0114] The difference from Example 2 is that the density of the electrolyte is 1.10 g / cm 3, calculated by mass percentage, includes the following components: 80% solvent, 6% additive, 14% LiPF6; the solvent is a mixture of ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and ethyl acetate in a mass ratio of 5:2:1:2, and the additive is a mixture of vinylene carbonate, fluoroethylene carbonate, and lithium difluorophosphate in a mass ratio of 4:1:1.
[0115] Therefore, the V S =0.1215cm 3 / g, that is, the ineffective pore porosity H of the positive electrode membrane c % is 8.46%; V s =0.1598cm 3 / g, that is, the ineffective porosity H of the negative electrode membrane a % is 10.03%, that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the positive electrode membrane are H c % / H a %=1.19.
[0116] Example 5
[0117] The difference from Example 2 is that the density of the electrolyte is 1.25 g / cm 3 , calculated by mass percentage, includes the following components: 80% solvent, 6% additive, 14% LiPF6; the solvent is a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a mass ratio of 6:2:2, and the additive is a mixture of vinylene carbonate, fluoroethylene carbonate, and lithium difluorophosphate in a mass ratio of 4:1:1.
[0118] Therefore, the V S =0.1082cm 3 / g, that is, the ineffective pore porosity H of the positive electrode membrane c % is 11.49%; V s =0.1345cm 3 / g, that is, the ineffective porosity H of the negative electrode membrane a % is 13.83%, that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the positive electrode membrane are H c % / H a %=1.20.
[0119] Example 6
[0120] A fast-charging AA or AAA lithium-ion battery, see attached Figure 1On the basis of satisfying the structure of Example 1, a first insulating device 7 and a second insulating device 8 are arranged on the upper and lower sides of the control circuit board 3, so that the components on the control circuit board 3 can be isolated and insulated from the positive and negative terminals of the battery cell 2 to avoid internal short circuit of the battery, and also play a role in protecting and supporting the control circuit board 3.
[0121] In addition, the ineffective pore porosity H of the positive electrode membrane in the battery cell 2 is c % is 8.23%, and the ineffective pore porosity H of the negative electrode membrane a % is 9.23%, that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the positive electrode membrane are H c % / H a %=1.12.
[0122] The filling coefficient of battery cell 2 is 2.65 g / Ah.
[0123] The density of the electrolyte is 1.22 g / cm 3 , calculated by mass percentage, includes the following components: 80% solvent, 5.5% additive, 14.5% LiPF6; the solvent is a mixture of ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and ethyl acetate in a mass ratio of 6:2:2:1, and the additive is a mixture of vinylene carbonate, fluoroethylene carbonate, and lithium difluorophosphate in a mass ratio of 4:1:1.
[0124] The preparation of the above-mentioned battery cell 2 comprises the following steps:
[0125] (1) Preparation of positive electrode plate 21: PVDF is dissolved in N-methylpyrrolidone (NMP) to obtain a uniform glue solution, and then carbon nanotubes and carbon black SP are dispersed in the above glue solution in turn by ultrasonic-assisted mechanical stirring, and finally lithium iron phosphate is added to perform slurrying and sieving under vacuum conditions to obtain a positive electrode slurry with a viscosity of 7756 mPa·s; the mass ratio of lithium iron phosphate, carbon black SP, carbon nanotubes, and PVDF is 96.7:1.5:0.5:1.3; the slurrying refers to homogenizing the slurry at room temperature using a stirring paddle that can move up and down, the stirring speed is 500 rpm, and the time is 0.5 h; the BET specific surface area of the lithium iron phosphate is 12.4 m 2 / g, tap density TD is 1.1g / cm 3 The positive electrode binder PVDF manufacturer is SOLVAF, the carbon black SP, and the carbon nanotube manufacturer is Yiruishi Graphite and Carbon.
[0126] The positive electrode slurry was then scraped onto both sides of the aluminum foil to obtain a positive electrode coating, which was then placed in an oven at 80°C and dried until the weight loss of the positive electrode coating reached 60% to 70% of the weight loss when dried to constant weight. The positive electrode coating was then taken out for cold pressing, and then vacuum dried at 120°C to constant weight. The compacted density was 2.38 g / cm 3 The positive electrode sheet; the cold pressing temperature is 25°C, the pressure is 0.2MPa, and the cold pressing time is 60s.
[0127] (2) Preparation of negative electrode sheet 22: Graphite, carbon black SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR are mixed in a mass ratio of 96.4:1.5:1.2:0.9, deionized water is added and stirred under vacuum to prepare a negative electrode slurry with a solid content of 55%; the specific surface area of the graphite is 1.74 m 2 / g, tap density TD is 1.16g / cm 3 The CMC manufacturer is Japan Daicel, and the SBR manufacturer is Japan Aiyulong.
[0128] The negative electrode slurry was uniformly coated on both sides of the copper foil to obtain a negative electrode coating, which was placed in an oven at 80°C and dried until the weight loss of the negative electrode coating reached 60% to 70% of the weight loss when dried to constant weight. Then, the negative electrode coating was taken out for cold pressing, and then vacuum dried at 120°C to constant weight. After cutting, the compacted density was 1.6 g / cm 3 The negative electrode sheet; the cold pressing temperature is 25°C, the pressure is 0.2MPa, and the cold pressing time is 60s.
[0129] (3) The positive electrode sheet 21, the separator 23, the negative electrode sheet 22 and the like are stacked in order and wound to form a bare cell. The bare cell is fixed in the steel shell by spot bottom welding, and after drying, the electrolyte is injected according to the injection coefficient, and then the cap is welded, sealed, left to stand, degassed, formed and aged to obtain the cell 2. The separator is a ceramic-coated PP separator with a thickness of 12 μm.
[0130] The V S =0.1056cm 3 / g, V of negative electrode film s =0.1273cm 3 / g.
[0131] Example 7
[0132] A fast-charging AA or AAA lithium-ion battery, which differs from Example 1 in that "a socket 11 compatible with the Type C charging interface 33 is provided on the shell 1" is changed to "a socket 41 compatible with the Type C charging interface 33 is provided on the upper sealing cover 4", that is, the Type C charging interface passes through the upper sealing cover 4 and is connected to the outer surface of the battery.
[0133] In addition, the ineffective pore porosity H of the positive electrode membrane in the battery cell 2 is c % is 14.99%, and the ineffective pore porosity H of the negative electrode membrane a % is 9.23%, that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the positive electrode membrane are H c % / H a %=0.62.
[0134] The injection coefficient and electrolyte of the battery cell 2 are the same as those of the sixth embodiment.
[0135] The preparation of the above-mentioned battery cell 2 comprises the following steps:
[0136] (1) Preparation of positive electrode plate 21: PVDF is dissolved in N-methylpyrrolidone (NMP) to obtain a uniform glue solution, and then carbon nanotubes and carbon black SP are dispersed in the above glue solution in turn by ultrasonic-assisted mechanical stirring, and finally lithium iron phosphate is added to perform slurrying and sieving under vacuum conditions to obtain a positive electrode slurry with a viscosity of 7648 mPa·s; the mass ratio of lithium iron phosphate, carbon black SP, carbon nanotubes, and PVDF is 95.1:1.5:0.5:2.9; the slurrying refers to homogenizing the slurry at room temperature using a stirring paddle that can move up and down, the stirring speed is 500 rpm, and the time is 0.5 h; the BET specific surface area of the lithium iron phosphate is 11.3 m 2 / g, tap density TD is 1.22g / cm 3 The positive electrode binder PVDF manufacturer is SOLVAF, the carbon black SP, and the carbon nanotube manufacturer is Yiruishi Graphite and Carbon.
[0137] The positive electrode slurry was then scraped onto both sides of the aluminum foil to obtain a positive electrode coating, which was then placed in an oven at 80°C and dried until the weight loss of the positive electrode coating reached 80% to 90% of the weight loss when dried to constant weight. The positive electrode coating was then taken out for cold pressing, and then vacuum dried at 120°C to constant weight. The compacted density was 2.31 g / cm 3 The positive electrode sheet; the cold pressing temperature is 25°C, the pressure is 0.2MPa, and the cold pressing time is 60s.
[0138] (2) Preparation of negative electrode sheet 22: the same as in Example 6.
[0139] (3) Assembly of battery cell 2: Same as Example 6
[0140] The V S =0.0880cm 3 / g, V of negative electrode film s =0.1273cm 3 / g.
[0141] Example 8
[0142] A fast-charging AA or AAA lithium-ion battery, which differs from Example 7 in that "a socket 11 compatible with the Type C charging interface 33 is provided on the shell 1" is changed to "a socket 41 compatible with the Type C charging interface 33 is provided on the upper sealing cover 4", that is, the Type C charging interface passes through the upper sealing cover 4 and is connected to the outer surface of the battery.
[0143] In addition, the ineffective pore porosity H of the positive electrode membrane in the battery cell 2 is c % is 11.45%, and the ineffective pore porosity H of the negative electrode membrane a % is 13.64%, that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the positive electrode membrane are H c % / H a %=1.19.
[0144] The filling coefficient of battery cell 2 is 3.17 g / Ah.
[0145] The density and composition of the electrolyte are the same as those in Example 1, which is 1.17 g / cm 3 .
[0146] The preparation of the above-mentioned battery cell 2 comprises the following steps:
[0147] (1) Preparation of positive electrode plate 21: PVDF is dissolved in N-methylpyrrolidone (NMP) to obtain a uniform glue solution, and then carbon nanotubes and carbon black SP are dispersed in the above glue solution in turn by ultrasonic-assisted mechanical stirring, and finally lithium iron phosphate is added to perform slurrying under vacuum conditions and sieve the material to obtain a positive electrode slurry with a viscosity of 7214 mPa·s; the lithium iron phosphate, carbon black SP, carbon nanotubes, and PVDF are in a mass ratio of 95:1.5:0.5:3; the slurrying refers to homogenizing the slurry at room temperature using a stirring paddle that can move up and down, the stirring speed is 500 rpm, and the time is 0.5 h; the BET specific surface area of the lithium iron phosphate is 11.3 m 2 / g, tap density TD is 1.22g / cm 3 The positive electrode binder PVDF manufacturer is SOLVAF, the carbon black SP, and the carbon nanotube manufacturer is Yiruishi Graphite and Carbon.
[0148] The positive electrode slurry was then scraped onto the two sides of the aluminum foil to obtain a positive electrode coating, which was then placed in an oven at 80°C and dried until the weight loss of the positive electrode coating reached 70% to 80% of the weight loss when dried to constant weight. The positive electrode coating was then taken out for cold pressing, and then vacuum dried at 120°C to constant weight. The compacted density was 2.30 g / cm 3 The positive electrode sheet; the cold pressing temperature is 25°C, the pressure is 0.2MPa, and the cold pressing time is 60s.
[0149] (2) Preparation of negative electrode sheet 22: Graphite, carbon black SP, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR are mixed in a mass ratio of 94.7:1.5:1.8:2, deionized water is added and stirred under vacuum to prepare a negative electrode slurry with a solid content of 55%; the specific surface area of the graphite is 1.95 m 2 / g, tap density TD is 1.04g / cm 3 The CMC manufacturer is Japan Daicel, and the SBR manufacturer is Japan Aiyulong.
[0150] The negative electrode slurry was uniformly coated on both sides of the copper foil to obtain a negative electrode coating, which was placed in an oven at 80°C and dried until the weight loss of the negative electrode coating reached 60% to 70% of the weight loss when dried to constant weight. Then, the negative electrode coating was taken out for cold pressing, and then vacuum dried at 120°C to constant weight. After cutting, the compacted density was 1.48 g / cm 3 The negative electrode sheet; the cold pressing temperature is 25°C, the pressure is 0.2MPa, and the cold pressing time is 70s.
[0151] (3) Same as Example 6.
[0152] The V S =0.1050cm 3 / g, V of negative electrode film s =0.1435cm 3 / g.
[0153] Comparative Example 1
[0154] The difference from Example 8 is that the ineffective pore porosity H of the positive electrode membrane is c % is 15.78%; that is, the ineffective pore porosity of the positive electrode membrane and the ineffective pore porosity of the positive electrode membrane are H a % / H c %=0.86.
[0155] When preparing the positive electrode sheet, the current collector coated with the positive electrode slurry is dried until the weight loss of the positive electrode coating reaches 70% to 80% of the weight loss when dried to constant weight, and then taken out for cold pressing. The compacted density of the obtained positive electrode sheet is 2.42 g / cm 3 , V of the positive electrode film S =0.0680cm 3 / g.
[0156] Preparation of the positive electrode plate 21: PVDF is dissolved in N-methylpyrrolidone (NMP) to obtain a uniform glue solution, and then carbon nanotubes and carbon black SP are dispersed in the above glue solution in turn by ultrasonic-assisted mechanical stirring, and finally lithium iron phosphate is added to perform pulping and sieving under vacuum conditions to obtain a positive electrode slurry with a viscosity of 7960 mPa·s; the lithium iron phosphate, carbon black SP, carbon nanotubes, and PVDF are in a mass ratio of 94.7:1.5:0.5:3.3; the pulping refers to homogenizing the slurry at room temperature using a stirring paddle that can move up and down, with a stirring speed of 500 rpm and a time of 0.5 h; the BET specific surface area of the lithium iron phosphate is 13.8 m 2 / g, tap density TD is 0.92g / cm 3 The positive electrode binder PVDF manufacturer is SOLVAF, the carbon black SP, and the carbon nanotube manufacturer is Yiruishi Graphite and Carbon.
[0157] The positive electrode slurry was then scraped onto both sides of the aluminum foil to obtain a positive electrode coating, which was then placed in a 120°C oven and vacuum dried until constant weight was reached. The coating was then taken out for cold pressing and cut to obtain a compacted density of 2.42 g / cm 3 The positive electrode sheet; the cold pressing temperature is 25°C, the pressure is 0.2MPa, and the cold pressing time is 90s.
[0158] The electrical performance of the battery cells prepared in the above examples and comparative examples was tested:
[0159] Test Case 1 Rate Performance
[0160] The rate performance test of the battery cells prepared in the embodiment and the comparative example comprises the following steps:
[0161] (1) Carry out 1C calibration test on the battery cell at room temperature;
[0162] (2) The battery cell is discharged at a constant current of 1C to 2.0V and left to stand for 60min. The battery cell is charged at a constant current of 1C, 4C, 8C, and 15C to 3.7V, and then charged at a constant voltage to 0.05C. The constant current charging time and charging capacity are counted to calculate the constant current ratio; constant current ratio = constant current charging capacity / (constant current charging capacity + constant voltage charging capacity) × 100%.
[0163] The constant current ratio can reflect the characteristics of the battery during the charging and discharging process, especially the efficiency and stability in the constant current stage. A higher constant current ratio usually means that the battery charges or discharges faster in the constant current stage and the battery has better performance.
[0164] The charging constant current ratio and total charging capacity of the battery cell are shown in Table 1.
[0165] Test Example 2 Cyclic Stability
[0166] The battery cells prepared in the examples and comparative examples were subjected to a cycle stability test, comprising the following steps:
[0167] (1) Carry out 1C calibration test on the battery cell at room temperature;
[0168] (2) The battery cell is discharged at a constant current of 4C to 2.0V and left to stand for 60min; it is charged at a constant current of 4C to 3.7V, and then charged at a constant voltage to 0.05C cut-off and left to stand for 60min;
[0169] (3) Repeat step (2) to perform a cell cycle test and calculate the capacity retention rate after different cycle numbers.
[0170] Table 1
[0171]
[0172] From the data in Table 1, it can be seen that the constant current ratio of the battery cell prepared in the embodiment of the present invention is higher than that of the comparative example, indicating that the positive electrode membrane of the battery cell provided by the present invention satisfies the ineffective pore porosity H c When % is lower than 15%, it has a good charging rate and can achieve fast charging.
[0173] Comparison of Examples 1 to 3 shows that when the negative electrode membrane remains unchanged, the H c The lower the H of the positive electrode film, the higher the constant current ratio of the battery cell, but the worse the cycle performance. The comprehensive performance of Example 2 is the best. c The lower the H%, the more transmission paths there are for lithium ions or electrons, which is more conducive to improving the charge and discharge efficiency. c A too low % indicates a low content of the binder, which easily leads to pores between the components of the positive electrode membrane or between the positive electrode membrane and the current collector, increasing the internal resistance, and the battery polarization becomes more serious with the cycle. The Ha% / Hc% of Example 2 is 1.17, which is within the preferred range of 1.12 to 1.17, so it can take into account both good rate performance and cycle performance.
[0174] Comparing Examples 2, 4, and 5, it can be seen that the components and density of the electrolyte have an impact on the ineffective pore porosity of the positive and negative electrode membranes. Specifically, the components and density of the electrolyte will affect its wettability to the membrane, resulting in changes in the electrolyte absorption of the positive and negative electrode membranes, and then causing changes in the ineffective pore porosity of the positive and negative electrode membranes. The lower the density of the electrolyte, the better the wettability to the membrane, so the greater the electrolyte absorption of the membrane; but due to the difference in wettability between the positive and negative electrode membranes, the density of the electrolyte is nonlinear to Ha% / Hc%. The test results show that the larger or too small the electrolyte density will cause Ha% / Hc% to fall out of the preferred range of 1.12 to 1.17. Therefore, the cycle stability of Examples 4 and 5 is lower than that of Example 2. This is because Ha% / Hc% falls out of the preferred range, which reduces the matching of the lithium ion or electron migration rate of the positive and negative electrodes, resulting in battery polarization.
[0175] In Examples 1 to 3, the ineffective pore porosity of the positive electrode sheet is controlled by regulating the weight loss rate in the normal pressure drying stage when preparing the positive electrode sheet. When the weight loss rate is 70% to 80% (Example 2), the obtained Ha% / Hc% meets the preferred range, taking into account good rate performance and cycle performance. When the weight loss rate is 50% to 60% (Example 1), due to the large amount of solvent remaining in the positive electrode film layer, the volume expands too much during the subsequent vacuum drying, and the amount of ineffective pores increases; when the weight loss rate is 60% to 70% (Example 3), due to the small amount of solvent remaining in the positive electrode film layer at this time, the fluidity of the components during cold pressing decreases, and the effect of improving the compaction density and eliminating ineffective pores decreases.
[0176] The positive electrode membranes of Example 1 and Example 7 have the same compaction density, but due to the different electrolyte components and densities, the components and preparation processes of the positive electrode membranes are different, which ultimately leads to different ineffective pore porosities, thereby affecting their rate performance.
[0177] Test Example 3 High Power Charging Performance
[0178] The charging time test of the batteries prepared in the examples and comparative examples comprises the following steps:
[0179] (1) Before assembling into batteries, discharge the cells at 4C constant current to 2.0V, and then assemble into AA batteries;
[0180] (2) The battery was charged at 18 W (5 V / 3 A), 30 W (15 V / 2 A), and 60 W (20 V / 3 A), respectively, and the time required to charge to 80% SOC was recorded. The results are listed in Table 2.
[0181] The charging stability test of the batteries prepared in the examples and comparative examples comprises the following steps:
[0182] (1) Before assembling into batteries, discharge the cells at 4C constant current to 2.0V, and then assemble into AA batteries;
[0183] (2) After fully charging the battery at 18W (5V / 3A), let it stand for 60 minutes, then discharge it at a constant current of 1C to 3V and let it stand for 60 minutes. The above is one cycle. After 600 cycles, the charge capacity retention rate is measured = the full charge capacity of the first week ÷ the full charge capacity of the 600th week × 100%.
[0184]
[0185] From the data in Table 1, it can be seen that the charging time of the battery is positively correlated with the constant current ratio of the battery cell, that is, the greater the constant current ratio of the battery cell, the better the fast charging performance of the battery prepared therefrom. In addition, the battery cell prepared by the present invention has good compatibility with the battery, and the capacity retention rate of the battery can still be maintained at a high level, indicating that the battery cell prepared by the present invention can be used to prepare AA or AAA batteries with fast charging performance, and the cost is low.
[0186] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A fast-charging AA or AAA lithium-ion battery, characterized in that: It comprises a shell, a battery cell arranged in the shell, a control circuit board, an upper sealing cover and a lower sealing cover for sealing the shell; the battery cell comprises a positive terminal on the upper side and a negative terminal on the lower side; a positive cap is welded on the top of the control circuit board, and a positive connecting piece is welded on the bottom of the control circuit board, and the positive connecting piece abuts against the positive terminal; the positive cap passes through the upper sealing cover and seals the control circuit board between the upper sealing cover and the battery cell together with the upper sealing cover; a charging interface and a charging protection circuit are arranged on the control circuit board, and a jack adapted to the charging interface is arranged on the shell or the upper sealing cover; The battery cell is provided with a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film sheet provided on at least one surface of the positive electrode current collector and comprising lithium iron phosphate, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode film sheet provided on at least one surface of the negative electrode current collector and comprising graphite; The ineffective pore porosity H of the positive electrode membrane c % is less than 15%, the ineffective porosity H c % is defined as the ratio of the volume of invalid pores in the positive electrode membrane to the total volume of the positive electrode membrane, wherein the invalid pores refer to the volume of the space in the positive electrode membrane that cannot be infiltrated by the electrolyte except the lithium iron phosphate body; The density of the electrolyte is 1.1-1.25 g / cm 3 .
2. A fast-chargeable AA or AAA lithium-ion battery according to claim 1, characterized in that: The ineffective pore porosity H of the negative electrode membrane a % is 9~14%, the ineffective pore porosity H a % is defined as the ratio of the volume of ineffective pores in the negative electrode membrane to the total volume of the negative electrode membrane. The ineffective pores refer to the volume of the space in the negative electrode membrane other than the graphite body that cannot be wetted by the electrolyte.
3. A fast-chargeable AA or AAA lithium-ion battery according to claim 2, characterized in that: The battery cell meets at least one of the following conditions 1 to 7: Condition 1: The ineffective pore porosity H of the positive electrode membrane c % satisfies 8% to 12%; Condition 2: The ineffective pore porosity H of the positive electrode membrane c % and the ineffective pore porosity H of the negative electrode membrane a %Satisfy H a % / H c % = 1.12 ~ 1.17; Condition 3: Compacted density PD of positive electrode c 2.25~2.40g / cm 3 ; Condition 4: Compacted density PD of negative electrode a 1.40~1.60g / cm 3 ; Condition 5: Invalid Porosity in, PD c The compaction density of the positive electrode; ρ c is the true density of lithium iron phosphate, which is 3.6 g / cm 3 ; V S is the electrolyte absorption volume per unit mass of the positive electrode membrane, in cm 3 / g; Condition 6: Invalid Porosity in, PD a is the compaction density of the negative electrode; ρ a is the true density of graphite, which is 2.26 g / cm 3 ; V s is the electrolyte absorption volume per unit mass of the negative electrode membrane, in cm 3 / g; Condition seven: The electrolyte comprises, by mass percentage, 13% to 15% lithium salt, 5% to 6% additives and 79% to 81% solvents, wherein the solvent comprises at least one of ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, fluorobenzene and ethyl acetate; the additive comprises at least one of vinylene carbonate, vinyl sulfate, propane sultone, fluoroethylene carbonate and lithium difluorophosphate; and the lithium salt is LiPF6.
4. A fast-chargeable AA or AAA lithium-ion battery according to any one of claims 1 to 3, characterized in that: The battery cell meets at least one of the following conditions eight to fourteen: Condition 8: The positive electrode current collector is aluminum foil; Condition 9: The negative electrode current collector is copper foil; Condition 10: The positive electrode membrane also includes a positive electrode binder and a positive electrode conductor, and the mass ratio of lithium iron phosphate, positive electrode conductor and positive electrode binder is 95-97:1.5-2.5:1-3; the positive electrode binder is PVDF, and the positive electrode conductor is at least one of carbon black, acetylene black, carbon nanotubes and graphene. Condition 11: The negative electrode membrane also includes a negative electrode binder and a negative electrode conductor, and the mass ratio of graphite, negative electrode conductor and negative electrode binder is 94.5-96.5:1-2:1-1.8:0.9-2; the negative electrode binder is at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid binder, and the negative electrode conductor is at least one of carbon black, acetylene black, carbon nanotubes and graphene. Condition 12: The electrolyte injection coefficient is 2.6-3.2 g / Ah; Condition 13: The specific surface area of the lithium iron phosphate is 10 to 15 m 2 / g, tap density TD is 0.8~1.5g / cm 3 ; Condition 14: The BET specific surface area of the graphite is 1 to 2.2 m 2 / g, tap density TD is 1~1.3g / cm 3 .
5. A fast-chargeable AA or AAA lithium-ion battery according to any one of claims 1 to 4, characterized in that: A negative electrode connecting piece is arranged between the negative electrode terminal and the lower sealing cover, and one end of the negative electrode connecting piece abuts against the negative electrode terminal, and the other end of the negative electrode connecting piece abuts against the lower sealing cover.
6. A fast-chargeable AA or AAA lithium-ion battery according to any one of claims 1 to 5, characterized in that: The lithium-ion battery also meets at least one of the following characteristics 1 to 4: Feature 1: The charging protection circuit includes a voltage stabilizing circuit and a charging control circuit; Feature 2: A first insulating device is provided between the upper sealing cover and the control circuit board; Feature 3: A second insulating device is provided between the control circuit board and the battery cell; Feature 4: The charging interface is a Lightning interface or a Type C interface.
7. A fast-chargeable AA or AAA lithium-ion battery according to any one of claims 1 to 5, characterized in that: The method for preparing the battery core comprises the following steps: (1) lithium iron phosphate, a positive electrode conductive agent, a positive electrode binder and a solvent 1 are mixed to prepare a positive electrode slurry, the positive electrode slurry is coated on a positive electrode current collector, and the positive electrode sheet is obtained after drying, pressing, slitting and sheeting; (2) mixing graphite, a negative electrode conductive agent, and a negative electrode binder, adding solvent 2 and stirring to prepare a negative electrode slurry, coating the negative electrode slurry on a negative electrode current collector, drying, pressing, slitting, and sheeting to obtain a negative electrode sheet; (3) stacking the positive electrode sheet, the separator, and the negative electrode sheet in order and winding them to form a bare cell; (4) The bare battery cell is fixed in the steel shell by spot bottom welding, and the electrolyte is injected after drying. Then, the battery cell is obtained by cap welding, sealing, standing, degassing, forming and aging.
8. A fast-chargeable AA or AAA lithium-ion battery according to any one of claim 7, wherein the drying and pressing comprises: The current collector coated with the positive electrode slurry or the negative electrode slurry is dried until the weight loss is 50% to 90% of the weight loss when dried to constant weight, and then taken out for pressing; then it is further dried to constant weight and pressed again.
9. A fast-charged AA or AAA lithium-ion battery according to any one of claim 8, wherein the pressing conditions are: the pressing temperature is lower than 25°C, the pressing pressure is 0.1-0.5 MPa, and the pressing time is 60-120 seconds.
10. A fast-charged AA or AAA lithium-ion battery according to any one of claim 7, wherein the solvent 1 is N-methylpyrrolidone NMP, and the solvent 2 is deionized water.
Citation Information
Patent Citations
Pole piece roll-forming method and device
CN103325993A
Drying device and rolling mechanism thereof, coating machine and pole piece coating and drying method
CN115846164A
Active particulate matter for preparing pole piece, battery pole piece as well as preparation method and application of active particulate matter
CN118117033A
Rechargeable lithium battery capable of being automatically produced
CN221282179U